Postpartum Day 4 Midwifery Care For Mrs. "D" With Pain From Post-Cesarean Section (Sc) In Bungi Health Center - Dina Purnama; Hilda Sulistia Alam; Wa Ode Sitti Justin (International Journal of Multidisciplinary Learners, 2024)
Background: Post SC suture wound pain is discomfort or pain felt by the mother at the suture wound in the abdomen after SC surgery to deliver a baby. Objective: This study aims to provide midwifery care to postpartum women with post-SC suture wound pain at the Baubau City Bungi Health Center using Varney’s 7-step documentation and SOAP. Methods: This type of research is a case study report, using Varney’s 7-step midwifery approach and SOAP documentation method. Results: Evaluation of the mother has known her condition, uterine contractions. Mother understands the condition of her wound and is willing to take medicine, relaxation, light activity, good nutrition. Maintain personal hygiene, change pads, and check herself if there are danger signs of puerperium. Husband and family provide support. Mother will return in 3 days for dressing change. Actions have been documented. Conclusions : Post partum midwifery care on day 4 on Mrs. “D” with post SC suture wound pain is carried out according to midwifery service standards.